2023
DOI: 10.14814/phy2.15770
|View full text |Cite
|
Sign up to set email alerts
|

A review of the biological effects of Myrtus communis

Mohammad Mahdi Dabbaghi,
Mohammad Saleh Fadaei,
Hesan Soleimani Roudi
et al.

Abstract: Myrtaceae is a family of woody flowering plants with approximately 5500 species divided into 144 genera and 17 tribes. In this family, the tribe Myrteae includes half of the family's biodiversity, with 51 genera and approximately 2500 species found primarily in the Neotropics. Myrtus is the only genus found in Europe, North Africa, Asia, and especially in the Mediterranean region of southern Europe as far west as Macaronesia (Madeira and the Azores), the Saharan mountains, and as far east as western Asia (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 130 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…This medicinal plant species is evergreen and local inhabitants of Kohistan use its leaves to treat eczema. In addition, M. communis is also used as tea, and flavoring agent in traditional cuisines of Kohistan (Amin et al [ 1 ]) and has been reported as a medicinal plant in the neighboring regions [ 96 , 97 ]. Beside this, Sambucus wightiana, Punica granatum, Quercus semecarpifolia, Astragalus anisacanthus, Persicaria capitata, Polygonum aviculare, and Polypodium sibiricum had maximum RFC.…”
Section: Resultsmentioning
confidence: 99%
“…This medicinal plant species is evergreen and local inhabitants of Kohistan use its leaves to treat eczema. In addition, M. communis is also used as tea, and flavoring agent in traditional cuisines of Kohistan (Amin et al [ 1 ]) and has been reported as a medicinal plant in the neighboring regions [ 96 , 97 ]. Beside this, Sambucus wightiana, Punica granatum, Quercus semecarpifolia, Astragalus anisacanthus, Persicaria capitata, Polygonum aviculare, and Polypodium sibiricum had maximum RFC.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies that elaborated on various aspects of the therapeutic potential of M. communis include Dabbaghi et al ( 2023 ) that states that myrtle’s strong antioxidant concentration is one of its most important defensive qualities. Research have demonstrated that myrtle’s antioxidant qualities can offer defense against dangerous compounds like pesticides, heavy metals, and other pollutants found in the environment.…”
Section: Toxicity and Side Effectsmentioning
confidence: 99%
“…In traditional folk medicine, a decoction made from the leaves and fruits is employed as a stomachic, hypoglycemic agent, and a antimicrobial substance. The plant is used to address issues such as coughs, oral diseases, and constipation, and it is used as an appetizer [ 24 , 25 ]. M. communis L. is rich in phenolic compounds like myricetine, gallic acid, vanillic acid, catechins, arbutin, and syringic acid [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plant is used to address issues such as coughs, oral diseases, and constipation, and it is used as an appetizer [ 24 , 25 ]. M. communis L. is rich in phenolic compounds like myricetine, gallic acid, vanillic acid, catechins, arbutin, and syringic acid [ 25 ]. Different authors have described the antioxidant activity of these extracts by introducing MCLE into food products.…”
Section: Introductionmentioning
confidence: 99%